Modeling / Optimization and Effect of Environmental Variables on Energy Production Based on PV / Wind Turbine Hybrid System - Alayi, Reza; Javad Velayti, Javad (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2021)
The use of fossil fuels to supply human energy needs is increasing day by day, which contributes to environmental pollution. In addition, they have a limited supply and are not continuously being made, or they are made very slowly. Thus, to reduce human dependence on this type of energy, the use of renewable energy sources is increasing, which has problems because of the high cost of investment and the stochastic nature. In this study, a sensitivity analysis of renewables was conducted to evaluate the impact of these resources on the costs of hybrid power plants based on renewable energies. In this regard, the amount of wind and intensity of sunlight was studied in the Kermanshah region. Significant results can be attributed to a reduction in the rate of return of capital to 9.22 years for the radiation intensity of 4.5Kwh / m2 / d. Then, by Sensitivity analysis to wind intensity, the Optimal wind turbine speed was 4.99 m/s, for COE 0.93($/Kwh).